DETERMINATION OF MICROBIOLOGICAL RISKS AT RESEARCH OF PIGS’ MEAT, INFESTED BY SARCOCYSTIS - Гавриленко, О. С.; Хоміцька, О. А.; Загорулько, О. В. (Scientific Progress & Innovations, 2015)
In the article the approaches to the microbiological risk assessment of pork, that was obtained from animals infected by sarcocystis, were described. The analysis of microbiological hazards of pigs’ meat infected by sarcocystis, included quantitative and qualitative information of microbiological hazards in materials research. We found that in samples with different degree of defeat by sarcocystis not only the number of mesophilic aerobic and facultative anaerobic microorganisms (MAFAM) in meat increases, but the number of pathogenic and conditional-pathogenic microorganisms.